Near-surface phosphorus-doped platinum-carbon fuel cell catalyst and preparation method thereof
By introducing 0.5 to 7 wt% of the phosphorus element into the platinum carbon catalyst of the fuel cell and doping it on the near surface inside the platinum nanoparticles, the problem of low catalyst stability is solved, and higher ORR stability and longer service life is achieved.
Patent Information
- Application Number
- CN202411826650.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
AI Technical Summary
The existing fuel cell platinum-based catalysts have problems with low stability, especially in long-term testing where base metal dissolution and nafion are toxic, resulting in poor ORR stability of the catalyst.
Using a platinum carbon fuel cell catalyst with near-surface phosphorus doping, the electronic structure of the platinum surface is regulated by introducing 0.5 to 7 wt% of the phosphorus element into the platinum carbon catalyst, the ORR performance is enhanced, and the phosphorus is doped on the near-surface inside the Pt nanoparticles through a one-step preparation method.
It significantly improves the electrochemical stability of the catalyst, avoids lattice expansion and phosphorus dissolution, extends the service life of the catalyst, and reduces production costs.
Smart Images

Figure CN119650731A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fuel cells and relates to a near-surface phosphorus-doped platinum-carbon fuel cell catalyst, a near-surface phosphorus-doped platinum-carbon fuel cell catalyst and a preparation method thereof. Background Art
[0002] With the development of economy, energy crisis is becoming more and more serious, and the development of green energy conversion technology has gradually attracted wide attention from all over the world. As an energy conversion device, proton exchange membrane fuel cell (PEMFC) can convert chemical energy into electrical energy while achieving zero carbon emission, and is an effective power generation device for realizing the application of hydrogen energy. However, limited by the slow electrode kinetics, the commercial application of fuel cells and hydrogen energy is relatively slow. In the face of this problem, precious metal platinum-based catalysts have gradually come into people's view. Among them, traditional platinum-carbon catalysts have the problem of high loading and low activity, and platinum-based catalysts will have base metal dissolution in long-term testing, thereby poisoning nafion, reducing proton conduction in the catalytic layer, and causing poor catalyst stability. Based on this, non-metallic doped platinum-carbon catalysts have begun to attract people's attention. The non-metallic elements doped in the catalyst can regulate the electronic structure of the platinum surface and enhance the ORR performance. At the same time, such catalysts do not have base metal dissolution in long-term testing, and nafion will not be poisoned, thereby greatly improving the ORR stability of the catalyst.
[0003] CN111224116A discloses a method for preparing a nitrogen-doped metal nitrogen-carbon catalyst, which introduces nitrogen into the catalyst, wherein the activity of the nitrogen-doped platinum-carbon catalyst is much better than that of the platinum-carbon catalyst before doping, proving that nitrogen promotes the activity of the catalyst. However, nitrogen has too strong electronegativity, which will cause the lattice expansion of platinum nanoparticles, thereby reducing the ORR stability of the catalyst.
[0004] The platinum-based catalysts for fuel cells disclosed in the prior art all have certain defects and the problem of low stability. Therefore, it is very important to develop and design a new type of platinum-based catalyst for fuel cells. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a near-surface phosphorus-doped platinum-carbon fuel cell catalyst and a preparation method thereof. The near-surface phosphorus-doped platinum-carbon fuel cell catalyst provided by the present invention has high electrochemical stability, and its stability is greatly improved compared with platinum-carbon catalysts without non-metal doping and with non-metal doping such as N.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a near-surface phosphorus-doped platinum-carbon fuel cell catalyst. Based on the mass of the platinum-carbon fuel cell catalyst as 100%, the Pt content in the platinum-carbon fuel cell catalyst is 20-62wt%, the non-metallic P content is 0.5-7wt%, and the remainder is a carbon carrier.
[0008] In the present invention, taking the mass of the platinum-carbon fuel cell catalyst as 100%, the Pt content in the platinum-carbon fuel cell catalyst is 20-62wt%, for example, it can be 20wt%, 22wt%, 25wt%, 28wt%, 30wt%, 32wt%, 35wt%, 38wt%, 40wt%, 42wt%, 45wt%, 48wt%, 50wt%, 52wt%, 55wt%, 58wt%, 60wt% or 62wt%, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0009] In the present invention, based on the mass of the platinum-carbon fuel cell catalyst as 100%, the non-metallic P content in the platinum-carbon fuel cell catalyst is 0.5-7wt%, for example, it can be 0.5wt%, 0.7wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt% or 7wt%, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0010] The near-surface phosphorus-doped platinum-carbon fuel cell catalyst provided by the present invention has high electrochemical stability, and its stability is greatly improved compared with platinum-carbon catalysts without non-metallic doping and non-metallic doping such as N. This is because the electronegativity of phosphorus is weak, and its electronic structure can regulate the oxygen reduction performance of the platinum-carbon catalyst without causing too much change in the platinum nanoparticle crystals.
[0011] Preferably, based on the mass of the platinum-carbon fuel cell catalyst as 100%, the Pt content in the platinum-carbon fuel cell catalyst is 40-62wt%, the non-metallic P content is 2-5wt%, and the remainder is the carbon carrier.
[0012] In the present invention, taking the mass of the platinum-carbon fuel cell catalyst as 100%, the Pt content in the platinum-carbon fuel cell catalyst is 40-62wt%, for example, it can be 40wt%, 42wt%, 44wt%, 46wt%, 48wt%, 50wt%, 52wt%, 54wt%, 56wt%, 58wt%, 60wt% or 62wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0013] In the present invention, taking the mass of the platinum-carbon fuel cell catalyst as 100%, the non-metallic P content in the platinum-carbon fuel cell catalyst is 2 to 5wt%, for example, it can be 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0014] Preferably, the Pt in the platinum-carbon fuel cell catalyst exists in the form of Pt nanoparticles and is distributed on the surface of the carbon carrier.
[0015] Preferably, the average particle size of the Pt nanoparticles is 2 to 6 nm, for example, it can be 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 5.5 nm or 6 nm, but it is not limited to the listed values. Other unlisted values within this numerical range are also applicable, preferably 2.5 to 4.5 nm; when the average particle size of the Pt nanoparticles is 2 to 6 nm, it has a higher specific surface area and electrochemical active area. Too large or too small a particle size will cause a loss in fuel cell performance.
[0016] Preferably, the non-metallic P in the platinum-carbon fuel cell catalyst is doped near the surface of the Pt nanoparticles in the form of single atoms and is located below 1 to 2 atomic layers on the surface of the Pt nanoparticles.
[0017] In the platinum-carbon fuel cell catalyst provided by the present invention, phosphorus is doped near the surface of the platinum nanoparticles to ensure the optimization effect on the catalyst performance while avoiding the lattice expansion caused by the formation of PtP crystal phase, thereby further improving the stability of the platinum-carbon fuel cell catalyst; if phosphorus is doped on the surface, phosphorus will be dissolved, reducing the optimization effect of phosphorus on the catalyst performance; if phosphorus is doped in the bulk phase, PtP crystal phase will be formed, resulting in lattice expansion, affecting the performance of the platinum-carbon fuel cell catalyst.
[0018] In a second aspect, the present invention provides a method for preparing the platinum-carbon fuel cell catalyst according to the first aspect, the preparation method comprising:
[0019] Water, a platinum precursor, a carbon carrier and a phosphorus precursor are mixed, and the water is removed by evaporation to obtain a residual solid P-Pt / C catalyst precursor; the obtained P-Pt / C catalyst precursor is heat-treated in a reducing atmosphere to obtain a platinum-carbon fuel cell catalyst.
[0020] The evaporation method described in the present invention includes rotary evaporation.
[0021] The preparation method of the platinum-carbon fuel cell catalyst provided by the present invention adopts a non-organic solvent system to prepare the catalyst, does not need to use an organic solvent, does not generate organic waste liquid, is environmentally friendly, and is suitable for large-scale production; in addition, the preparation method adopts a one-step method to achieve the preparation of the phosphorus-doped catalyst, that is, a platinum precursor and a phosphorus precursor are added to the reaction together, so that the synthesis of platinum-carbon and phosphorus doping can be completed at the same time, and there is no need to synthesize platinum-carbon first and then dope with phosphorus. The preparation process is simple, which reduces the production cost of the platinum-carbon fuel cell catalyst, and at the same time, the non-metallic P can be doped in the form of a single atom near the surface inside the Pt nanoparticle.
[0022] Preferably, the mixing comprises:
[0023] Platinum precursor, carbon carrier and phosphorus precursor are added into water, and ultrasonic dispersion and stirring are performed in sequence to obtain mixed slurry.
[0024] Preferably, the stirring is carried out at 15-30°C, for example, 15°C, 17°C, 20°C, 22°C, 25°C, 27°C or 30°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] Preferably, the stirring time is 3 to 36 hours, for example, it can be 3 hours, 6 hours, 9 hours, 12 hours, 15 hours, 18 hours, 21 hours, 24 hours, 27 hours, 30 hours, 33 hours or 36 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably 12 to 24 hours.
[0026] Preferably, the reducing atmosphere includes reducing gas and protective gas.
[0027] Preferably, the volume fraction of the reducing gas in the reducing atmosphere is 2 to 10%, for example, it can be 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] The reducing atmosphere described in the present invention may be, for example, a mixed atmosphere of hydrogen and argon, or a mixed atmosphere of hydrogen and nitrogen, but is not limited to the listed atmospheres. Any reducing atmosphere composed of a reducing gas and a protective gas in the prior art may be applicable.
[0029] Preferably, the heat treatment includes sequential heating and heat preservation.
[0030] Preferably, the heating rate is 1-10°C / min, and the terminal temperature is 300-700°C, preferably 400-500°C.
[0031] The heating rate described in the present invention is 1 to 10°C / min, for example, it can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] The terminal temperature of the heating in the present invention is 300-700°C, for example, it can be 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C or 700°C, but is not limited to the listed values. Other unlisted values within the numerical range are also applicable, preferably 400-500°C.
[0033] Preferably, the insulation time is 2 to 10 hours, for example, it can be 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] Preferably, the platinum precursor includes any one of chloroplatinic acid, sodium chloroplatinate, potassium chloroplatinate, sodium chloroplatinite, potassium chloroplatinite, platinum tetrachloride, tetraammine platinum nitrate, potassium chloroplatinite or potassium hexaiodineplatinate, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of chloroplatinic acid and sodium chloroplatinate, a combination of potassium chloroplatinate and sodium chloroplatinite, a combination of sodium chloroplatinite and potassium chloroplatinite, a combination of tetraammine platinum nitrate and potassium chloroplatinite, a combination of potassium chloroplatinite and potassium hexaiodineplatinate, or a combination of chloroplatinic acid, sodium chloroplatinate and potassium chloroplatinate.
[0035] Preferably, the carbon carrier comprises any one of carbon black, graphite, graphene, carbon fiber, carbon nanotubes, activated carbon or carbon molecular sieve or a combination of at least two thereof. Typical but non-limiting combinations include a combination of carbon black and carbon black, a combination of graphite and graphene, a combination of carbon fiber and carbon nanotubes, a combination of activated carbon and carbon molecular sieves, a combination of carbon black, carbon black and graphite, or a combination of graphene, carbon fiber, carbon nanotubes and activated carbon.
[0036] Preferably, the model of the carbon black includes any one of commercially available EC300-JD, EC600-JD, XC-72 or BP2000 or a combination of at least two thereof, and a typical but non-limiting combination includes a combination of EC300-JD and EC600-JD, a combination of XC-72 and BP2000, or a combination of EC300-JD, EC600-JD and XC-72.
[0037] Preferably, the phosphorus precursor includes any one of sodium dihydrogen phosphate, potassium dihydrogen phosphate, magnesium dihydrogen phosphate, lithium dihydrogen phosphate, aluminum dihydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, ammonium phosphate, sodium phosphate, potassium phosphate, sodium pyrophosphate, potassium pyrophosphate, sodium metaphosphate, potassium metaphosphate, phosphoric acid, pyrophosphoric acid or metaphosphoric acid, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of sodium dihydrogen phosphate and potassium dihydrogen phosphate, a combination of magnesium dihydrogen phosphate and lithium dihydrogen phosphate, a combination of aluminum dihydrogen phosphate and ammonium dihydrogen phosphate, a combination of diammonium hydrogen phosphate and disodium hydrogen phosphate, a combination of dipotassium hydrogen phosphate and ammonium phosphate, a combination of sodium phosphate and potassium phosphate, a combination of sodium pyrophosphate, potassium pyrophosphate and sodium metaphosphate, or a combination of potassium metaphosphate, phosphoric acid, pyrophosphoric acid and metaphosphoric acid.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] (1) The near-surface phosphorus-doped platinum-carbon fuel cell catalyst provided by the present invention has a high electrochemical stability, which is greatly improved compared with platinum-carbon catalysts without non-metallic doping or non-metallic doping such as N. This is because the electronegativity of phosphorus is relatively weak, and its electronic structure can regulate the oxygen reduction performance of the platinum-carbon catalyst without causing significant changes in the platinum nanoparticle crystals;
[0040] (2) In the platinum-carbon fuel cell catalyst provided by the present invention, phosphorus is doped near the surface of the platinum nanoparticles to ensure the optimization effect on the catalyst performance while avoiding the lattice expansion caused by the formation of PtP crystal phase, thereby further improving the stability of the platinum-carbon fuel cell catalyst; if phosphorus is doped on the surface, phosphorus will be dissolved, reducing the optimization effect of phosphorus on the catalyst performance; if phosphorus is doped in the bulk phase, PtP crystal phase will be formed, resulting in lattice expansion, affecting the performance of the platinum-carbon fuel cell catalyst;
[0041] (3) The method for preparing the platinum-carbon fuel cell catalyst provided by the present invention adopts a non-organic solvent system to prepare the catalyst, does not require the use of organic solvents, does not generate organic waste liquid, is environmentally friendly, and is suitable for large-scale production;
[0042] (4) The preparation method provided by the present invention adopts a one-step method to achieve the preparation of the phosphorus-doped catalyst, that is, the platinum precursor and the phosphorus precursor are added to the reaction together, so that the synthesis of platinum carbon and phosphorus doping can be completed at the same time, without the need to synthesize platinum carbon first and then dope with phosphorus. The preparation process is simple, which reduces the production cost of platinum-carbon fuel cell catalysts. At the same time, non-metallic P can also be doped in the near-surface of the Pt nanoparticles in the form of single atoms. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is the XRD pattern of the platinum-carbon fuel cell catalyst provided in Example 1.
[0044] Figure 2 This is a TEM image of the platinum-carbon fuel cell catalyst provided in Example 1.
[0045] Figure 3 This is the XRD pattern of the platinum-carbon fuel cell catalyst provided in Comparative Example 5.
[0046] Figure 4 This is a comparison chart of the initial ORR polarization curves of the platinum-carbon fuel cell catalyst provided in Example 1 and the commercial Pt / C catalyst provided in Comparative Example 6.
[0047] Figure 5 This is a comparison chart of the initial ORR polarization curve of the platinum-carbon fuel cell catalyst provided in Example 1, the ORR polarization curve after 10,000 cycles, the ORR polarization curve after 20,000 cycles, and the ORR polarization curve after 30,000 cycles.
[0048] Figure 6 This is a comparison chart of the initial CV curve, the CV curve after 10,000 cycles, the CV curve after 20,000 cycles, and the CV curve after 30,000 cycles of the platinum-carbon fuel cell catalyst provided in Example 1.
[0049] Figure 7 The bar graphs are of the mass specific activity and area specific activity of the platinum-carbon fuel cell catalyst provided in Example 1 at 0.9 V vs. RHE in the initial state, after 10,000 cycles, after 20,000 cycles, and after 30,000 cycles.
[0050] Figure 8 The initial ORR polarization curve of the platinum-carbon fuel cell catalyst provided for Comparative Example 5. DETAILED DESCRIPTION
[0051] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0052] Example 1
[0053] This embodiment provides a near-surface phosphorus-doped platinum-carbon fuel cell catalyst, where the mass of the platinum-carbon fuel cell catalyst is 100%, the Pt content in the platinum-carbon fuel cell catalyst is 59.8wt%, the non-metallic P content is 3.2wt%, and the remainder is a carbon carrier;
[0054] The Pt in the platinum-carbon fuel cell catalyst exists in the form of Pt nanoparticles and is distributed on the surface of the carbon carrier; the average particle size of the Pt nanoparticles is 2.6 nm;
[0055] In the platinum-carbon fuel cell catalyst, non-metallic P is doped near the surface of the Pt nanoparticle in the form of single atoms and is located below 1 to 2 atomic layers on the surface of the Pt nanoparticle.
[0056] The preparation method of the platinum-carbon fuel cell catalyst comprises:
[0057] Chloroplatinic acid, EC300-JD carbon black and sodium dihydrogen phosphate are added to water and ultrasonically dispersed, and the obtained mixed slurry is stirred for 14 hours to obtain a mixed slurry; the mixed slurry is then subjected to rotary evaporation to remove water, and then vacuum dried at 80°C to obtain a P-Pt / C catalyst precursor; the obtained P-Pt / C catalyst precursor is heated to 500°C at a rate of 5°C / min in a reducing atmosphere composed of hydrogen and argon, and then kept warm for 2 hours, wherein the volume fraction of hydrogen in the reducing atmosphere is 5%, to obtain a platinum-carbon fuel cell catalyst.
[0058] Example 2
[0059] This embodiment provides a near-surface phosphorus-doped platinum-carbon fuel cell catalyst, where the mass of the platinum-carbon fuel cell catalyst is 100%, the Pt content in the platinum-carbon fuel cell catalyst is 50.1wt%, the non-metallic P content is 4.3wt%, and the remainder is a carbon carrier;
[0060] The Pt in the platinum-carbon fuel cell catalyst exists in the form of Pt nanoparticles and is distributed on the surface of the carbon carrier; the average particle size of the Pt nanoparticles is 2.5 nm;
[0061] In the platinum-carbon fuel cell catalyst, non-metallic P is doped near the surface of the Pt nanoparticle in the form of single atoms and is located below 1 to 2 atomic layers on the surface of the Pt nanoparticle.
[0062] The preparation method of the platinum-carbon fuel cell catalyst comprises:
[0063] Sodium chloroplatinite, BP2000 carbon black and potassium dihydrogen phosphate are added to water and ultrasonically dispersed, and the obtained mixed slurry is stirred for 18 hours to obtain a mixed slurry; the mixed slurry is subjected to rotary evaporation to remove water, and then vacuum dried at 80°C to obtain a P-Pt / C catalyst precursor; the obtained P-Pt / C catalyst precursor is heated to 450°C at a rate of 5°C / min in a reducing atmosphere composed of hydrogen and nitrogen, and then kept warm for 6 hours, wherein the volume fraction of hydrogen in the reducing atmosphere is 6%, to obtain a platinum-carbon fuel cell catalyst.
[0064] Example 3
[0065] This embodiment provides a near-surface phosphorus-doped platinum-carbon fuel cell catalyst, where the mass of the platinum-carbon fuel cell catalyst is 100%, the Pt content in the platinum-carbon fuel cell catalyst is 40.2wt%, the non-metallic P content is 5.0wt%, and the remainder is a carbon carrier;
[0066] The Pt in the platinum-carbon fuel cell catalyst exists in the form of Pt nanoparticles and is distributed on the surface of the carbon carrier; the average particle size of the Pt nanoparticles is 2.8 nm;
[0067] In the platinum-carbon fuel cell catalyst, non-metallic P is doped near the surface of the Pt nanoparticle in the form of single atoms and is located below 1 to 2 atomic layers on the surface of the Pt nanoparticle.
[0068] The preparation method of the platinum-carbon fuel cell catalyst comprises:
[0069] Sodium chloroplatinate, graphite and dipotassium hydrogen phosphate are added into water and ultrasonically dispersed, and the obtained mixed slurry is stirred for 24 hours to obtain a mixed slurry; the mixed slurry is subjected to rotary evaporation to remove water, and vacuum drying is performed at 80°C to obtain a P-Pt / C catalyst precursor; the obtained P-Pt / C catalyst precursor is heated to 400°C at a rate of 3°C / min in a reducing atmosphere composed of hydrogen and argon, and then kept warm for 8 hours, wherein the volume fraction of hydrogen in the reducing atmosphere is 4%, to obtain a platinum-carbon fuel cell catalyst.
[0070] Example 4
[0071] This embodiment provides a near-surface phosphorus-doped platinum-carbon fuel cell catalyst, where the mass of the platinum-carbon fuel cell catalyst is 100%, the Pt content in the platinum-carbon fuel cell catalyst is 20.8wt%, the non-metallic P content is 1.9wt%, and the remainder is a carbon carrier;
[0072] The Pt in the platinum-carbon fuel cell catalyst exists in the form of Pt nanoparticles and is distributed on the surface of the carbon carrier; the average particle size of the Pt nanoparticles is 4.1 nm;
[0073] In the platinum-carbon fuel cell catalyst, non-metallic P is doped near the surface of the Pt nanoparticle in the form of single atoms and is located below 1 to 2 atomic layers on the surface of the Pt nanoparticle.
[0074] The preparation method of the platinum-carbon fuel cell catalyst comprises:
[0075] Potassium chloroplatinate, XC-72 carbon black and potassium dihydrogen phosphate are added to water and ultrasonically dispersed, and the obtained mixed slurry is stirred for 36 hours to obtain a mixed slurry; the mixed slurry is then subjected to rotary evaporation to remove water, and then vacuum dried at 80°C to obtain a P-Pt / C catalyst precursor; the obtained P-Pt / C catalyst precursor is heated to 500°C at a rate of 1°C / min in a reducing atmosphere composed of hydrogen and nitrogen, and then kept warm for 10 hours, wherein the volume fraction of hydrogen in the reducing atmosphere is 2%, to obtain a platinum-carbon fuel cell catalyst.
[0076] Example 5
[0077] The present embodiment provides a near-surface phosphorus-doped platinum-carbon fuel cell catalyst. Taking the mass of the platinum-carbon fuel cell catalyst as 100%, the Pt content in the platinum-carbon fuel cell catalyst is 58.2wt%, the non-metallic P content is 3.3wt%, and the average particle size of the Pt nanoparticles is 2.5nm. In addition, the preparation method of the platinum-carbon fuel cell catalyst is the same as Example 1, except that the sodium dihydrogen phosphate is replaced by dipotassium hydrogen phosphate.
[0078] Example 6
[0079] The present embodiment provides a near-surface phosphorus-doped platinum-carbon fuel cell catalyst. Taking the mass of the platinum-carbon fuel cell catalyst as 100%, the Pt content in the platinum-carbon fuel cell catalyst is 59.3wt%, the non-metallic P content is 3.5wt%, and the average particle size of the Pt nanoparticles is 2.8nm. In addition, the preparation method of the platinum-carbon fuel cell catalyst is the same as that in Example 1, except that chloroplatinic acid is replaced with potassium chloroplatinate.
[0080] Example 7
[0081] The present embodiment provides a near-surface phosphorus-doped platinum-carbon fuel cell catalyst. Taking the mass of the platinum-carbon fuel cell catalyst as 100%, the Pt content in the platinum-carbon fuel cell catalyst is 59.1wt%, the non-metallic P content is 3.3wt%, and the average particle size of the Pt nanoparticles is 3.0nm. In addition, EC300-JD carbon black in the preparation method of the platinum-carbon fuel cell catalyst is replaced with XC-72 carbon black. The rest is the same as Example 1.
[0082] Example 8
[0083] The present embodiment provides a near-surface phosphorus-doped platinum-carbon fuel cell catalyst, in which the average particle size of the Pt nanoparticles is 2.1 nm, the Pt content in the platinum-carbon fuel cell catalyst is 58.3 wt %, and the non-metallic P content is 5.7%. That is, only the amount of sodium dihydrogen phosphate is increased in the preparation method of the platinum-carbon fuel cell catalyst, and the rest is the same as Example 1.
[0084] Example 9
[0085] The present embodiment provides a near-surface phosphorus-doped platinum-carbon fuel cell catalyst, in which the average particle size of the Pt nanoparticles is 5.1 nm, the Pt content in the platinum-carbon fuel cell catalyst is 58.7 wt %, and the non-metallic P content is 0.7%. That is, only the amount of sodium dihydrogen phosphate is reduced in the preparation method of the platinum-carbon fuel cell catalyst, and the rest is the same as Example 1.
[0086] Example 10
[0087] The present embodiment provides a near-surface phosphorus-doped platinum-carbon fuel cell catalyst, in which the average particle size of the Pt nanoparticles is 2.1 nm, the Pt content in the platinum-carbon fuel cell catalyst is 57.8 wt %, and the non-metallic P content is 4.7%. That is, only the terminal temperature of the heating in the preparation method of the platinum-carbon fuel cell catalyst is changed, that is, the insulation temperature is adjusted to 300°C, and the rest is the same as Example 1.
[0088] Embodiment 11
[0089] The present embodiment provides a near-surface phosphorus-doped platinum-carbon fuel cell catalyst, in which the average particle size of the Pt nanoparticles is 6.0 nm, the Pt content in the platinum-carbon fuel cell catalyst is 58.6 wt %, and the non-metallic P content is 5.9%. That is, only the terminal temperature of the heating in the preparation method of the platinum-carbon fuel cell catalyst is changed, that is, the insulation temperature is adjusted to 700°C, and the rest is the same as Example 1.
[0090] Comparative Example 1
[0091] This comparative example provides a near-surface phosphorus-doped platinum-carbon fuel cell catalyst, which is the same as Example 1 except that the Pt content in the platinum-carbon fuel cell catalyst is 59.4wt%, the non-metallic P content is 0.3wt%, and the average particle size of the Pt nanoparticles is 10.3nm, that is, only the amount of chloroplatinic acid added in the preparation method of the platinum-carbon fuel cell catalyst is reduced.
[0092] Comparative Example 2
[0093] This comparative example provides a near-surface phosphorus-doped platinum-carbon fuel cell catalyst, in which the Pt content in the platinum-carbon fuel cell catalyst is 59.4wt%, the non-metallic P content is 15wt%, and the average particle size of the Pt nanoparticles is 5.0nm, that is, only the amount of sodium dihydrogen phosphate added in the preparation method of the platinum-carbon fuel cell catalyst is increased, and the rest is the same as Example 1.
[0094] Comparative Example 3
[0095] This comparative example provides a platinum-carbon fuel cell catalyst, which is the same as Example 1 except that the Pt content in the platinum-carbon fuel cell catalyst remains unchanged, the non-metallic P content is 0wt%, and the average particle size of the Pt nanoparticles is 14.2nm, that is, sodium dihydrogen phosphate is not added in the preparation method of the platinum-carbon fuel cell catalyst.
[0096] Comparative Example 4
[0097] This comparative example provides a commercial Pt / C catalyst for a fuel cell.
[0098] The platinum-carbon fuel cell catalyst and commercial Pt / C catalyst provided in the above-mentioned embodiments and comparative examples were subjected to X-ray diffraction (XRD) testing. The testing method is as follows: the powder sample is evenly flattened in the groove of the quartz plate and placed in the testing instrument. The instrument tube voltage and tube current are adjusted to 40 kV and 15 mA respectively. The test angle is 10° to 90°, and the scanning speed is 5° / min. The platinum-carbon fuel cell catalyst and commercial Pt / C catalyst provided in the above-mentioned embodiments and comparative examples are tested using a transmission electron microscope (TEM). The XRD pattern of the platinum-carbon fuel cell catalyst provided in Example 1 is shown in FIG. Figure 1 As shown in the TEM image Figure 2 shown by Figure 1 and Figure 2 It can be seen that the Pt nanoparticles in the platinum-carbon fuel cell catalyst are uniformly dispersed on the carbon carrier, and the particles have high dispersion and uniformity; in addition, the XRD pattern of the platinum-carbon fuel cell catalyst provided in Comparative Example 5 is as follows Figure 3 As shown;
[0099] The platinum-carbon fuel cell catalyst and commercial Pt / C catalyst provided in the above examples and comparative examples were applied to a rotating disk electrode for testing. The testing method was as follows: 3 mg of the catalyst was dispersed in a mixture of 980 μL of isopropanol and deionized water, 20 μL of a 5% Nafion solution was added, and a dispersion was obtained after ultrasonic dispersion. The dispersion was dropwise applied to a disk electrode (0.2475 cm 2 ) and fully dried under a baking lamp to make 40μg Pt / cm 2 The electrode head with catalyst loading was used for electrochemical characterization test; the electrochemical characterization test was carried out in a standard three-electrode system, with a carbon rod as the counter electrode and a saturated calomel electrode as the reference electrode. The test was carried out at room temperature and in O 2 Saturated 0.1M HClO 4 The ORR polarization curve was measured in the electrolyte. 2 Saturated 0.1M HClO 4 The background CV curve was measured in the electrolyte; the specific scanning potential was 0.1~1.1V RHE,The scanning rate is 10mV / s;
[0100] The initial ORR half-wave potential of the platinum-carbon fuel cell catalyst and the commercial Pt / C catalyst obtained by electrochemical characterization test is shown in Table 1, and the attenuation amount of the half-wave potential after 30,000 cycles of accelerated attenuation and the attenuation ratio of the mass specific activity are shown in Table 1; wherein, the attenuation rate of mass specific activity = (initial mass specific activity - mass specific activity after 30,000 cycles of accelerated attenuation) / initial mass specific activity;
[0101] The initial ORR polarization curve comparison diagram (initial activity comparison diagram) of the platinum-carbon fuel cell catalyst provided in Example 1 and the commercial Pt / C catalyst provided in Comparative Example 6 is obtained by electrochemical characterization test. Figure 4 As shown;
[0102] The comparison diagram of the initial ORR polarization curve, the ORR polarization curve after 10,000 cycles, the ORR polarization curve after 20,000 cycles, and the ORR polarization curve after 30,000 cycles of the platinum-carbon fuel cell catalyst provided in Example 1 obtained by electrochemical characterization test is shown in FIG. Figure 5 As shown;
[0103] The comparison diagrams of the initial CV curve, the CV curve after 10,000 cycles, the CV curve after 20,000 cycles, and the CV curve after 30,000 cycles of the platinum-carbon fuel cell catalyst provided in Example 1 obtained by electrochemical characterization test are shown in the following figure. Figure 6 As shown;
[0104] The electrochemical characterization test obtained the mass specific activity and area specific activity of the platinum-carbon fuel cell catalyst provided in Example 1 at 0.9 V vs. RHE in the initial state, after 10,000 cycles, after 20,000 cycles, and after 30,000 cycles. Figure 7 As shown;
[0105] The initial ORR polarization curve of the platinum-carbon fuel cell catalyst provided in Comparative Example 5 was obtained by electrochemical characterization test. Figure 8 shown.
[0106] Table 1
[0107]
[0108]
[0109] From Table 1, we can get:
[0110] (1) The platinum-carbon fuel cell catalysts of the fuel cells provided in Examples 1 to 7 have a relatively high initial ORR half-wave potential, and the attenuation of the half-wave potential and the attenuation ratio of the mass specific activity are relatively small after 30,000 cycles of accelerated attenuation;
[0111] (2) By comparing Example 1 with Examples 8, 9, 10 and 11, it can be seen that the content of non-metallic P doped in the platinum-carbon fuel cell catalyst of the present invention and the catalyst calcination temperature will affect the average particle size of the Pt nanoparticles, thereby causing a certain impact on the performance of the platinum-carbon fuel cell catalyst. When the average particle size of the Pt nanoparticles is preferably 2.5 to 4.5 nm, it will be more conducive to having a higher specific surface area and electrochemical active area at the same time. Too large or too small a particle size will cause a loss in fuel cell performance;
[0112] (4) By comparing Example 1 with Comparative Examples 1 and 2, it can be seen that the non-metallic P content in the platinum-carbon fuel cell catalyst of the present invention will affect the performance of the platinum-carbon fuel cell catalyst. When the non-metallic P content is 0.5-7wt%, it is more conducive to obtaining a platinum-carbon fuel cell catalyst with better activity and higher stability. This is because too little P doping does not fully exert the regulating effect of P on the catalyst, while too much P doping will generate a PtP crystal phase, and the P in the bulk phase will cause the lattice expansion of the Pt nanoparticles, thereby affecting the ORR performance of the catalyst;
[0113] (5) By comparing Example 1 with Comparative Example 3, it can be seen that the excellent ORR performance of the platinum-carbon fuel cell catalyst of the present invention is due to the doping of phosphorus in the catalyst, which has a weak electronegativity and an electronic structure suitable for regulating the oxygen reduction performance of the catalyst, and basically does not change the platinum nanoparticle crystals; in addition, the excellent ORR performance of the platinum-carbon fuel cell catalyst is also due to the doping position of the phosphorus element. The phosphorus element is doped near the surface of the platinum nanoparticles, which can effectively prevent lattice expansion. At the same time, the doping position near the surface can reduce the loss of phosphorus in the test, so that the phosphorus element can optimize the performance of the catalyst for a long time; after removing the added phosphorus precursor, the Pt / C catalyst provided in Comparative Example 5 is synthesized. The particle size of the Pt nanoparticles in the Pt / C catalyst is very large, which is 14.2 nm. The particles show obvious agglomeration phenomenon, and its mass specific activity of 0.9V is 0.152AmgPt -1 , the particles agglomerate and are not suitable for actual fuel cells, which shows that phosphorus doping has a regulatory effect on the catalyst particle size and activity;
[0114] (6) By comparing Example 1 with Comparative Example 4, it can be seen that the electrochemical stability of the platinum-carbon fuel cell catalyst of the fuel cell provided by the present invention is relatively high, and its stability is greatly improved compared with the platinum-carbon catalyst without non-metallic doping and non-metallic doping such as N. This is because the electronegativity of phosphorus is relatively weak, and its electronic structure can regulate the oxygen reduction performance of the platinum-carbon catalyst without causing too much change in the platinum nanoparticle crystals;
[0115] In the platinum-carbon fuel cell catalyst provided by the present invention, phosphorus is doped near the surface of the platinum nanoparticles to ensure the optimization effect on the catalyst performance while avoiding the lattice expansion caused by the formation of PtP crystal phase, thereby further improving the stability of the platinum-carbon fuel cell catalyst; if phosphorus is doped on the surface, phosphorus will be dissolved, reducing the optimization effect of phosphorus on the catalyst performance; if phosphorus is doped in the bulk phase, PtP crystal phase will be formed, resulting in lattice expansion, affecting the performance of the platinum-carbon fuel cell catalyst; the preparation method of the platinum-carbon fuel cell catalyst provided by the present invention adopts a non-organic solvent system to prepare the catalyst, does not need to use an organic solvent, does not generate organic waste liquid, is environmentally friendly, and is suitable for large-scale production; in the preparation method provided by the present invention, a one-step method is used to prepare the phosphorus-doped catalyst, that is, a platinum precursor and a phosphorus precursor are added to the reaction together, so that the synthesis of platinum carbon and phosphorus doping can be completed at the same time, without the need to synthesize platinum carbon first and then dope with phosphorus, the preparation process is simple, the production cost of the platinum-carbon fuel cell catalyst is reduced, and at the same time, non-metallic P can be doped in the form of a single atom near the surface of the Pt nanoparticles.
[0116] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A near-surface phosphorus-doped platinum-carbon fuel cell catalyst, characterized in that: Taking the mass of the platinum-carbon fuel cell catalyst as 100%, the Pt content in the platinum-carbon fuel cell catalyst is 20-62wt%, the non-metallic P content is 0.5-7wt%, and the remainder is the carbon carrier.
2. The platinum-carbon fuel cell catalyst according to claim 1, characterized in that: Taking the mass of the platinum-carbon fuel cell catalyst as 100%, the Pt content in the platinum-carbon fuel cell catalyst is 40-62wt%, the non-metallic P content is 2-5wt%, and the remainder is the carbon carrier.
3. The platinum-carbon fuel cell catalyst according to claim 1 or 2, characterized in that: The Pt in the platinum-carbon fuel cell catalyst exists in the form of Pt nanoparticles and is distributed on the surface of the carbon carrier.
4. The platinum-carbon fuel cell catalyst according to claim 3, characterized in that: The average particle size of the Pt nanoparticles is 2 to 6 nm, preferably 2.5 to 4.5 nm.
5. The platinum-carbon fuel cell catalyst according to claim 3 or 4, characterized in that: In the platinum-carbon fuel cell catalyst, non-metallic P is doped in the form of single atoms near the inner surface of Pt nanoparticles and is located below 1 to 2 atomic layers on the surface of the Pt nanoparticles.
6. A method for preparing the platinum-carbon fuel cell catalyst according to any one of claims 1 to 5, characterized in that: The preparation method comprises: Water, a platinum precursor, a carbon carrier and a phosphorus precursor are mixed, and the water is removed by evaporation to obtain a residual solid P-Pt / C catalyst precursor; the obtained P-Pt / C catalyst precursor is heat-treated in a reducing atmosphere to obtain a platinum-carbon fuel cell catalyst.
7. The preparation method according to claim 6, characterized in that: The mixing includes: Platinum precursor, carbon carrier and phosphorus precursor are added into water, and ultrasonic dispersion and stirring are performed in sequence to obtain mixed slurry.
8. The preparation method according to claim 6 or 7, characterized in that: The reducing atmosphere includes reducing gas and protective gas; Preferably, the volume fraction of the reducing gas in the reducing atmosphere is 2-10%.
9. The preparation method according to any one of claims 6 to 8, characterized in that: The heat treatment includes heating and heat preservation in sequence; Preferably, the heating rate is 1-10°C / min, and the terminal temperature is 300-700°C, preferably 400-500°C; Preferably, the insulation time is 2 to 10 hours.
10. The preparation method according to any one of claims 6 to 9, characterized in that: The platinum precursor includes any one of chloroplatinic acid, sodium chloroplatinate, potassium chloroplatinate, sodium chloroplatinite, potassium chloroplatinite, platinum tetrachloride, tetraammine platinum nitrate, potassium chloroplatinite or potassium hexaiodideplatinate, or a combination of at least two thereof; Preferably, the carbon carrier comprises any one or a combination of at least two of carbon black, graphite, graphene, carbon fiber, carbon nanotube, activated carbon or carbon molecular sieve; Preferably, the phosphorus precursor includes any one of sodium dihydrogen phosphate, potassium dihydrogen phosphate, magnesium dihydrogen phosphate, lithium dihydrogen phosphate, aluminum dihydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, ammonium phosphate, sodium phosphate, potassium phosphate, sodium pyrophosphate, potassium pyrophosphate, sodium metaphosphate, potassium metaphosphate, phosphoric acid, pyrophosphate or metaphosphoric acid, or a combination of at least two thereof.
Citation Information
Patent Citations
Catalyst for fuel cell and preparation method thereof
CN111224116A
Cited By
Nano composite material based on porous carrier as well as preparation method and application of nano composite material
CN120109212A